IN-VITRO BIO-AVAILABILITY OF IRON FROM IRON FORTIFIED COW MILK-OAT MILK BLENDED YOGHURT - Pallavi, Dhavalagi; Hiremath, ayashri P.; NM, Madhusudan (International Journal of Clinical and Biomedical Research, 2016)
Yoghurt is a dairy product obtained by fermentation of milk using starter culture Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus. Application of dietary fibre and iron salt fortification in the manufacture of yoghurt enhances its nutritive and therapeutic value. Oat (Avena sativa) is a cereal that contains soluble fibre - glucan renders several health benefits. In the present investigation, an attempt was made to develop iron salt fortified, cow milk and oat milk blended yoghurt and in-vitro bioavailability of the iron from the yoghurt was explored. The optimization of oat milk tried at different levels and was accepted at 20% level and fortification of cow milk - oat milk blended yoghurt with ferrous sulphate fortified at different levels and was accepted at 10mg. Experimental yoghurt samples tested for sensory, chemical parameters, microbiological test and in-vitro bio-availability. The yoghurt samples showed (12%) of iron was maximum bio-availability from yoghurt fortified with ferrous sulphate followed by control and cow milk-oat milk blended yoghurt showed 10.2% and 8.52% respectively. The bio-availability of iron was reduced due to interfere of dietary fibre in yoghurt.